Technological-organisational-environmental (TOE) framework in industry 4.0 adoption among SMEs in Malaysia: an early outlook / Mira Qerul Barriah Muhamad, Syed Jamal Abdul Nasir Syed Mohamad and Norzanah Mat Nor - Muhamad, Mira Qerul Barriah; Syed Mohamad, Syed Jamal Abdul Nasir; Mat Nor, Norzanah (Universiti Teknologi MARA, 2021)
Presently, the fourth industrial revolution has already paved its way throughout many industries and left a dramatic impact on the way technology was adopted, the organisation operated and changed the business environment landscape. Since small and medium-sized enterprises (SMEs) in Malaysia have been one of the major backbones of the country’s economy, accounting for up to 37% of total GDP, it is crucial for them to adopt the infusion of automation and digital practices embedded in Industry 4.0 in order to remain competitive and innovative in the market. Although Industry 4.0 has been booming worldwide, it is still a challenge for small enterprises to adopt, especially in a developing country like Malaysia. Relationships between the technological, organisational, and environmental contexts as well as the adoption implementation of Industry 4.0 by small and medium-sized enterprises in Malaysia are the main criteria to be verified in this research. The aim is to explore and discuss the use of Technological-Organisational Environmental (TOE) framework in the analysis of factors that influence the adoption of Industry 4.0 by small and medium-sized enterprises (SMEs) in Malaysia.